Climate Change in Africa Adaptation, Resilience, and Policy Innovations - Addaney, Michael; Jarbandhan, D B.; Kwadwo Dumenu, William (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This edited collection chronicles the public policy responses to climate change and current and potential impacts that will affect critical and priority sectors within and across African countries now and in the coming decades. Contributions cover governance and policy responses to climate change, emphasizing continental governance and policy responses, national governance and policy responses (what selected countries in Africa are doing), and local or community policy and programmatic responses (what some selected major African communities are doing). Each chapter adopts multi-disciplinary and transdisciplinary approaches, combining insights from social and policy sciences, emphasizing existing gaps, particularly in the area of decision-making, governance and local climate action. The book offers both theoretical and practical contributions, with the aim of advancing academic discourse and thinking, policymaking and implementation of climate interventions in Africa. Michael Addaney is a lecturer in environmental planning at the Department of Land Management of University of Energy and Natural Resources, Ghana. Michael is also a Research Fellow of the Earth System Governance Project at Utrecht University, The Netherlands. DB (Vain) Jarbandhan is associate professor and the Director of the Centre for Public Management and Governance in the College of Business and Economics, University of Johannesburg, South Africa. William Kwadwo Dumenu is a research scientist at the Forestry Research Institute of Ghana and a Research Associate and Lecturer at the Sustainable Food System Institute, Rhine-Waal University of Applied Science, Germany.
Chapter 1. Climate change, adaptation policy and resilient development in Africa: Pathways and emerging innovations (Michael Addaney and Vain Jarbandhan) -- Part:1 -- Chapter 2. Climate change impediments to realising the right to development in Africa (Carol Chi Ngang) -- Chapter 3. Placing indigenous and experiential knowledge in climate change adaptation governance in Africa (Habib S Usman, Michael Addaney and Cephas Brewsters Soyapi) -- Chapter 4. Climate change adaptation governance in Africa: A state of the art Abstract (Marus Gbomagba) -- Chapter 5. Climate Change, REDD+ and Gender justice in Forest-Dependent Communities of Africa (Rachel Yeboah Nketiah) -- Chapter 6. Climate change mitigation and adaptation responses in the context of food and nutritional security in Africa (Jennifer Turyatemba Tumushabe) -- Part:2 -- Chapter 7. Multi-level climate change adaptation governance in Nigeria and South Africa (Olubunmi A. Afinowi) -- Chapter 8. Legal responses to climate disasters in Southern Africa: Practical legal developments in Zimbabwe and Mozambique (Lenin Tinashe Chisair) -- Chapter 9. Connecting climate change, disaster risk reduction and good governance in South Africa (Bethuel Sibongiseni Ngcamu and Evangelos Mantzaris) -- Chapter 10. Governing urban green spaces in the context of climate change in Ghana (Nelson Nyabanyi N-yanbini) -- Chapter 11. Carbon Ownership and Issues of Resource Governance in Ethiopia (Zenebe Mekonnen) -- Chapter 12. Climate Variability and Household Food security in the Guinea Savannah Agro-ecological Zone of Ghana (Seth Opoku Mensah, Timothy Amang-bey Akanpabadai, Michael Addaney, Seth Asare Okyere, and Stephen Kofi Diko).
Keywords: Environmental sciences -- Social aspects; Human geography; Sustainability; Environmental geography; Environmental Social Sciences; Human Geography; Sustainability; Integrated Geography